1992
DOI: 10.1002/cne.903240413
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of sensory hair cells in a fish ear

Abstract: The ultrastructure of sensory hair cells in the utricle of the cichlid fish, Astronotus ocellatus, the oscar, was studied by transmission electron microscopy of serial ultrathin sections from different regions of the epithelium. Two distinctly different types of hair cell were found, one located in the striolar region of the epithelium and the other in the extrastriolar region. Striolar hair cells have a well-defined perinuclear cisterna located just below the nucleus, and large perinuclear mitochondria. Synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
2
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 50 publications
1
44
2
1
Order By: Relevance
“…These cells are quite typical of those found in the ear and lateral line of other vertebrates (Chang et al 1992). The sensory hair cells have a cell body which is innervated by a¡erent (and sometimes e¡erent) neurons and an apically positioned bundle of cilia which project into the lumen of the ear.…”
Section: Sensory Cells Of the Earmentioning
confidence: 86%
See 2 more Smart Citations
“…These cells are quite typical of those found in the ear and lateral line of other vertebrates (Chang et al 1992). The sensory hair cells have a cell body which is innervated by a¡erent (and sometimes e¡erent) neurons and an apically positioned bundle of cilia which project into the lumen of the ear.…”
Section: Sensory Cells Of the Earmentioning
confidence: 86%
“…Work on a number of ¢sh species has supported the idea of there only being a single type of hair cell in anamniotes (reviewed in Chang et al 1992). Indeed, although studies in the 1980s hinted at the possibility of there being several types of hair cell in ¢shes, this was never explored in any depth and the variation was never considered as having functional signi¢cance (see Popper & Fay 1999 (a) Hair cell heterogeneity A number of studies have shown di¡erences in the responses of sensory hair cells in discrete locations in the utricle of the cichlid Astronotus ocellatus (the oscar) to treatment with the ototoxic drug gentamicin sulphate (Yan et al 1991) and to the calcium-binding antibody S-100 (Saidel et al 1990).…”
Section: Sensory Cells Of the Earmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been some reports of morphological and structural diversity of hair cells in the ear of anamniotes (Hama, 1969;Corwin, 1977;Popper and Hoxter, 1981;Wegner, 1982;Jensen, 1984), there was no clear evidence of a possible homology between the anamniote and amniote hair cell types until the recent discovery of two distinct types of sensory hair ceils in the ear of the teleost fish, Astronotus ocetlatus, the oscar (Saidel et al, 1990a, b;Yah et al, 1991;Chang et _., 1992). The two types of hair cell in the oscar ear, one in the striolar region and the other in the extrastriolar region of the utricle and the lagena, may be similar to amniote type I and type II hair cells, respectively.…”
mentioning
confidence: 99%
“…The sensory epithelia in both organs contain sensory hair ceils and supporting cells for detecting motion of surrounding water or fluid. Because of these similarities, the lateral line and the inner ear are collectively referred to as the octavolateralis system (Northcutt, 1980;McCormick, 1982;Popper et al, 1992 …”
mentioning
confidence: 99%